2019
DOI: 10.1097/gme.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ESR1 polymorphism with menopause and MLXIPL genetic variant influence serum uric acid levels in Slovak midlife women

Abstract: Objective: This study examines associations between the ESR1 (XbaI, PvuII) and the MLXIPL (rs3812316) gene polymorphisms, and uric acid (UA) levels in Slovak midlife women, subdivided according to their menopause status. Methods: We assessed a total of 362 women from 38 to 65 years of age. Women were recruited from different localities in the western and middle parts of Slovakia. Participants were interviewed during their medical examination at local he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Notably, CK and myoglobin are known to be correlated biomarkers. As for rs782312718 in MLXIPL gene, a cross-sectional study demonstrated an association between this gene and levels of serum uric acid [ 69 ]. All 5 homozygotes for this variant have uric acid levels below 5th percentile.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CK and myoglobin are known to be correlated biomarkers. As for rs782312718 in MLXIPL gene, a cross-sectional study demonstrated an association between this gene and levels of serum uric acid [ 69 ]. All 5 homozygotes for this variant have uric acid levels below 5th percentile.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from menopausal symptoms, other female reproductive histories have also been proven independently to be relevant to midlife health and psychosocial well-being. In particular, a history of miscarriage was identified as being associated with worsening sleep quality while the number of parities was relevant to severely depressed mood and lack of enjoyment 20. Other salient female reproductive histories such as the onset age of menarche and breast feeding have been recognised as being significantly associated with cardiovascular risk factors including obesity and obesity-related hypertension 21.…”
Section: Introductionmentioning
confidence: 99%